Effectiveness of non-invasive ventilation in patients with type 2 respiratory failure - Patel, Shahid M.; Nair, Girija P.; Tuppekar, Balaji G.; Uppe, Abhay G. (International Journal of Research in Medical Sciences, 2021)
Background: Assess the use of non-invasive ventilation as an alternative way for ventilation in acute respiratory failure, determine factors that can predict the successful use of NIV, evaluate factors hindering success of NIV. Methods: Thirty hospitalised patients fulfilling inclusion criteria, diagnosed with Type II Respiratory Failure on ABG were recruited after obtaining an informed written consent. Complete history and detailed physical examination were followed by routine investigations. Results: Comparison of the pH on admission with the pH after 1st hour of NIV, the latter showed statistically significant improvement. Drop in PaCo2 and rise in PaO2 on ABG from admission and after stopping NIV was statistically significant. Patients with lower MMRC grade and severe cough showed significant improvement in pH, however patient with higher emergency visits and past hospitalisation showed less improvement in pH, after 1 hour of NIV therapy. A total 4 patients were intubated, with mean pH of 7.22, 3 out of them had higher emergency visits, 2 out of them had ICU admission. Conclusions: NIV treatment for COPD with type II respiratory failure avoids intubation, reduces complications and should be considered as first line therapy instead of ET intubation. Lower mMRC grade, lesser hospitalizations, lesser emergency visits, higher BMI, symptoms like cough, can have a positive predictive value for the outcome of NIV.